Pengaruh Respon Dimensi Kurikulum Dan Metode Pembelajaran Terhadap Kepedulian Mahasiswa Pada Csr - Nafis, Rafidatun; Adam, Helmy (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to determine the effect of the response to the dimensions of the curriculum and learning methods on students’ awareness of Corporate Social Responsibility. Data are collected from questionnaires distributed to undergraduate students of Universitas Brawijaya, acquiring Corporate Social Responsibility knowledge from lectures. The samples include 205 respondents selected through purposive sampling technique, and are analyzed by using multiple linear regression. The results of the study prove that the dimensions of the curriculum and learning methods affect students’ awareness of Corporate Social Responsibility.